Increased osteoarthritis in moose from Isle Royale. - Peterson, R. O. (Journal of Wildlife Diseases, 1988)
Over the past 30 yr, moose (Alces alces) in Isle Royale National Park (Michigan, USA) exhibited a several-fold increase in the prevalence of osteoarthritis, or degenerative joint disease (DJD). Available evidence points to an environmental explanation for this change. Greater physical activity among afflicted moose is not a likely contributing factor, nor is genetic change in the population. The possible introduction of an unspecified disease agent cannot be dismissed at this time. Moose exhibiting the highest prevalence of DJD were those born during a period of severe undernutrition, and it is hypothesized that nutritional stress early in life was responsible for increased joint disease during senescence. Such an etiology for osteoarthritis has not been suggested previously for any species.